Observation, laser photocoagulation or anti-VEGF therapy in the management of retinal arterial macroaneurysms - Yuelin Wang; Hong Du; Xinyu Zhao; Lihui Meng; Youxin Chen (BMC Ophthalmology, 2022)
Abstract Background To explore the efficacy of observation, laser photocoagulation, and anti-VEGF in the management of retinal arterial macroaneurysm (RAM). Methods We retrospectively included patients diagnosed with RAM at the Peking Union Medical College Hospital (PUMCH) from 2003 to 2021, and comprehensively reviewed cases documented in the literature from multiple databases (PROSPERO protocol CRD42022310417). Patients were categorized into 3 groups: the observation group, anti-VEGF group, and laser photocoagulation group. LogMAR visual acuity (VA) and central retinal thickness (CMT) at the end of the follow-up were analyzed. Results A total of 14 patients from the PUMCH and 210 patients from the literature review were included. VA and CMT in patients who underwent observation, laser photocoagulation, and anti-VEGF therapies were significantly improved from baseline (p < 0.05), with changes in LogMAR VA improved by -0.34 ± 0.68, -0.17 ± 0.58, and -0.45 ± 0.62 and changes in CMT improved by -148.26 ± 138.99 µm, -185.61 ± 130.37 µm, and -287.45 ± 171.87 µm, respectively. Subgroup analysis revealed that anti-VEGF therapy was used in patients with worse VA than patients who underwent laser photocoagulation (p = 0.010), but achieved better improvement in VA than the laser photocoagulation group (p = 0.049). Patients treated with anti-VEGF also had thicker CMT than the observation group (p = 0.013), and experienced better changes in CMT than the observation, as well as laser photocoagulation groups (p = 0.005; p = 0.047). Conclusion Observation, anti-VEGF, and laser photocoagulation are effective therapeutic methods for the management of RAM, and anti-VEGF therapy is intended to better improve patients with severe VA and CMT.